A panoramic sunroof light control film for eliminating cabin reflection and a preparation process thereof
Patent Information
- Application Number
- CN202611217304.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-08-12
AI Technical Summary
[0004]该方案能降低部分反射率,却引入了新的光学界面:OCA胶层自身折射率与PET基材的折射率存在差异,在斜入射或宽光谱条件下仍会产生残余菲涅尔反射,无法根除倒影
1.座舱倒影产生的光学根源在于层叠结构内部存在折射率突变的宏观界面。现有技术采用OCA光学胶将AR膜与PET基材贴合,不可避免地引入了AR膜/胶层和胶层/PET基材两个附加的折射率跃变界面。即使胶层与PET的折射率差极小,根据菲涅尔公式,在斜入射或宽光谱条件下仍会产生可察觉的残余反射,叠加形成座舱内的人影或景物倒影。本发明则通过环氧开环反应,将AR膜与PET基材直接以共价键合为一体,消除了中间的宏观胶层界面。此时,虽然从AR膜高折射率层到改性PET之间,折射率不同,但由于是化学键连接,不存在离散的物理界面,光波在过渡区的反射被抑制,形成了一个亚光学波长的折射率渐变层。配合偏析剂实现的贴合面高密度环氧官能团定点反应,过渡区致密均匀,没有因胶层厚度不均或微小气泡引发的散射,从机理上消除了倒影产生的界面反射通道。
Smart Images

Figure CN122755282B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of dimming film technology, and in particular to a panoramic sunroof dimming film for eliminating cabin reflections and its preparation process. Background Technology
[0002] PDLC (polymer dispersed liquid crystal) dimming films are widely used in smart cockpits and panoramic sunroofs due to their excellent heat insulation, sun shading, and brightness switching functions. In existing technologies, large-area curved sunroofs can cause severe cabin reflections in strong sunlight, superimposing with the outside scenery, seriously interfering with the driver's and passengers' vision and reducing the perceived quality of the cabin.
[0003] To eliminate such reflections, existing technologies typically apply an AR (anti-reflective) film to the inside of the sunroof. Traditional solutions use OCA optical adhesive to bond the AR film to the PDLC substrate layer by layer, forming a stacked structure of AR film, OCA, PET substrate, ITO conductive layer, and PDLC functional layer.
[0004] This solution can reduce some reflectivity, but it introduces a new optical interface: the refractive index of the OCA adhesive layer differs from that of the PET substrate, resulting in residual Fresnel reflection under oblique incidence or broad-spectrum conditions, making it impossible to completely eliminate reflections. Furthermore, the acrylate backbone of OCA is prone to ester hydrolysis in the high-temperature and high-humidity environment of a vehicle, leading to yellowing of the adhesive layer, increased haze, and decreased peel strength, ultimately causing the entire film to fail.
[0005] On the other hand, conductive electrode systems also face challenges. ITO films are difficult to adapt to curved hot bending due to their brittleness, while PEDOT:PSS flexible electrodes, although highly conductive, have poor adhesion to PET substrates and usually require the application of an insulating primer to enhance adhesion. This insulating layer forms a charge transport barrier at the interface, leading to increased contact resistance and sheet resistance, ultimately resulting in increased PDLC drive voltage and power consumption.
[0006] In summary, existing technologies, due to their reliance on adhesive layers and insulating primers for interlayer bonding, introduce trade-offs in optical, mechanical, and electrical properties. Therefore, a novel interface design strategy is urgently needed to eliminate reflections and overcome performance bottlenecks. Summary of the Invention
[0007] The purpose of this invention is to address the shortcomings of existing technologies by proposing a panoramic sunroof dimming film for eliminating cabin reflections and its preparation process.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: This invention first proposes a panoramic sunroof dimming film to eliminate cabin reflections, which is stacked sequentially from the inside of the cabin to the outside of the vehicle as follows: modified AR anti-reflective film layer, modified PET substrate layer, PEDOT:PSS transparent conductive electrode layer, PDLC dimming function layer, PEDOT:PSS transparent conductive electrode layer, and outer substrate protective layer. The bonding surface of the modified AR antireflective film is enriched with epoxy functional groups by an epoxy segregating agent. The modified PET substrate has amino functional groups grafted onto the side facing the AR film, and the side facing the electrode is anchored with a long chain structure containing thiophene segments by a triethoxysilyl-terminated polythiophene oligomer. The modified AR antireflective film layer and the modified PET substrate layer are bonded together by a covalent bond structure formed by the ring-opening reaction of epoxy groups and amino groups without glue. The modified PET substrate is bonded to the interface formed by the thiophene segments and the PEDOT:PSS conjugated main chain; The outer substrate protective layer is a modified PET substrate facing the electrode.
[0009] Traditional OCA optical adhesive bonding relies solely on van der Waals forces for physical adhesion, which is the core cause of interface debonding and blistering under humid and hot aging. Furthermore, according to Fresnel's law of reflection, the greater the difference in refractive index between the two media, the higher the interface reflectivity. In traditional solutions, there are two additional reflective interfaces between the OCA adhesive layer (n≈1.48) and the AR high-refractive-index layer (n≈1.65) and the PET substrate (n≈1.57), which increases the total reflectivity, produces ghosting, and interferes with the anti-reflection effect.
[0010] In this solution, the epoxy groups on the AR film bonding surface undergo a ring-opening reaction with the amino groups on the PET substrate surface to form a molecular-level bond of CN covalent bonds. The OCA adhesive layer is eliminated, and the covalent bonding interface is a molecular-level transition with a continuous and gradual change in refractive index. This eliminates two additional reflective surfaces and further reduces the reflectivity on the cockpit side. However, because the OCA adhesive layer, which has an elastic buffering effect, is eliminated, the overall impact resistance is slightly reduced.
[0011] Preferably, the modified AR antireflective film has a double-layer interference structure, consisting of a low-refractive-index fluorinated acrylate layer on the air side, a high-refractive-index silicone acrylate layer on the bonding side, and an epoxy segregating agent added to the silicone acrylate layer. Epoxy functional groups are enriched on the bonding surface of the high-refractive-index layer through surface segregation, with an epoxy functional group density of 2.5–3.5 nmol / cm³. 2 ; The refractive index of the fluorinated acrylate layer is 1.37–1.39, and the dry film thickness is 85–95 nm; the refractive index of the organosilicon acrylate layer is 1.63–1.67, and the dry film thickness is 105–115 nm.
[0012] Preferably, the modification process of the modified PET substrate includes: The side facing the AR film is frequently etched with oxygen plasma and then grafted with γ-aminopropyltriethoxysilane. After the side facing the electrode is frequently etched with oxygen plasma to introduce hydroxyl groups, a triethoxysilane-terminated polythiophene oligomer is anchored, and its thiophene segments extend outward.
[0013] Preferably, the epoxy segregating agent is an epoxy-terminated fluorocarbon acrylate oligomer, and its preparation steps are as follows: Fluorinated acrylate monomers, epoxy acrylate monomers, and azobisisobutyronitrile initiator were weighed according to a mass ratio of 72-78:18-22:3-6, mixed, and then anhydrous ethanol was added to prepare a reaction system with a solid content of 20%. Free radical polymerization was carried out at a constant temperature of 78-82℃ for 7-9 hours under nitrogen protection. After precipitation with n-hexane and vacuum drying, epoxy segregating agent was obtained. The fluorinated acrylate monomer is hexafluorobutyl methacrylate or hexafluorobutyl acrylate; the epoxy acrylate monomer is glycidyl methacrylate. Where CH2=CR-COO-Rf is hexafluorobutyl methacrylate or hexafluorobutyl acrylate; The obtained epoxy segregating agent has a polyacrylate backbone, fluorinated alkyl and epoxy side chains. During the gradient drying stage after coating, the solvent evaporates, the system temperature rises, the molecular chain segment mobility is enhanced, and the low surface energy fluorinated side chains will spontaneously reduce the contact energy with the air interface, driving the entire segregating agent molecule to accumulate on the coating surface, while carrying the polar epoxy groups to the bonding surface to form a high density of reaction sites.
[0014] The number-average molecular weight of the epoxy segregating agent is 1500-2500, the epoxy equivalent is 700-900, the fluorine content is 15-20wt%, and the surface energy is ≤22mN / m. The preparation method of the triethoxysilyl-terminated polythiophene oligomer specifically includes the following steps: Under anhydrous and oxygen-free conditions, 2,5-dibromo-3-hexylthiophene was dissolved in dry tetrahydrofuran, and isopropyl magnesium chloride was added dropwise at low temperature to carry out Grignard exchange. The mixture was stirred at room temperature for 1 to 2 hours. Ni(dppp)Cl2 catalyst was added, and the temperature was raised to reflux to carry out Kumada cross-coupling polymerization. The degree of polymerization was controlled at 3 to 6 thiophene rings by controlling the molar ratio of 2,5-dibromo-3-hexylthiophene to isopropyl magnesium chloride at 30 to 50:1. After polymerization, the reaction was terminated by end capping with vinyl magnesium bromide, precipitated in methanol, purified and dried to obtain a polythiophene oligomer with vinyl at one end and hydrogen or bromine at the other end. Where n = 1 to 4; The halogen-metal exchange equilibrium reaction utilizes the alkyl magnesium bond of isopropyl magnesium chloride (i-PrMgCl) to exchange groups with the C-Br bond at the α-position of the thiophene ring, generating aryl Grignard active species in situ, which provides reaction sites for subsequent polymerization. Nickel-catalyzed catalytic transfer polymerization achieves controllable chain growth by having the nickel catalyst always bound to the end of the growing chain. The number of initial active species is controlled by adjusting the molar ratio of monomer to magnesium isopropyl chloride, and the conversion rate is limited by the reflux reaction time. Ultimately, the degree of polymerization is precisely controlled in the low-polymerization range of 3 to 6 thiophene units, avoiding the formation of high molecular weight polythiophene. The low degree of polymerization ensures that the molecular chain has sufficient mobility and can be fully entangled with the PEDOT:PSS backbone in the future. After the polymerization reaches the target degree of polymerization, monofunctional vinyl magnesium bromide is added as a terminator. It undergoes transmetallization with the aryl-Ni(II)-Br intermediate at the end of the growing chain, and then is eliminated by reduction. The vinyl group is covalently introduced into the ω end of the polythiophene chain, and the nickel catalyst is removed from the chain end, thus completely terminating the polymerization reaction. During the methanol precipitation process, the C-MgBr bond remaining at the other end of the chain is protonated by methanol to generate CH bond.
[0015] Polythiophene oligomers are obtained by converting vinyl groups to hydroxyl groups through a hydroboration-oxidation reaction; In the anti-Markovnikov electrophilic addition reaction, borane acts as an electrophile, adding to the carbon-carbon double bond of the vinyl group. The boron atom selectively adds to the terminal carbon with fewer substituents, generating a trialkylboron intermediate. Under alkaline hydrogen peroxide conditions, the CB bond of the trialkylboron is oxidized and rearranged into a CO bond. After hydrolysis, a terminal primary hydroxyl group (-CH2CH2OH) is generated. The hydroxyl group is located at the very end of the molecular chain, providing the only reaction site for subsequent silane grafting.
[0016] Hydroxyl-terminated polythiophene oligomers were dissolved in an anhydrous solvent. 3-isocyanate-propyltriethoxysilane and 2%–4% (by mass) of dibutyltin dilaurate (based on the total mass of 3-isocyanate-propyltriethoxysilane and the hydroxyl-terminated polythiophene oligomers) were added at a molar ratio of hydroxyl to isocyanate group = 1:1.1–1.3. The mixture was reacted at 60–70 °C for 4–6 hours, followed by vacuum distillation, purification, and drying to obtain triethoxysilyl-terminated polythiophene oligomers.
[0017] The nucleophilic addition reaction of hydroxyl groups with isocyanates produces carbamate bonds; The siloxane end of the triethoxysilyl-terminated polythiophene oligomer undergoes a condensation reaction with the hydroxyl groups on the surface of the PET substrate after hydrolysis, and is anchored to the substrate surface through Si-OC covalent bonds, while the other end of the thiophene long chain extends outward. During the film-forming and drying process of PEDOT:PSS, the PEDOT conjugated backbone will undergo molecular chain interpenetration and weak π-π stacking interactions with the anchored polythiophene long chain. The physical entanglement only acts on the hydrophobic conjugated region of the PEDOT backbone and does not chemically react with the sulfonic acid groups of PSS. It will not neutralize the doped charge carriers or break the conjugated backbone. Therefore, the conductivity retention rate is high, ensuring the light-diffusing uniformity of large-size skylights.
[0018] Preferably, the material specifications of each functional layer meet the following requirements: The dry film thickness of the PEDOT:PSS transparent conductive electrode is 90-110 nm, and the sheet resistance is 130-170 Ω / sq. The thickness of the PDLC dimming functional layer is 12-18 μm, wherein the mass ratio of nematic liquid crystal is 65%-75%, and the prepolymer is aliphatic polyurethane acrylate. The modified PET substrate layer has an optical-grade PET substrate with a thickness of 180–200 μm. The outer substrate protective layer is made of 120-130 μm thick optical-grade PET substrate.
[0019] This invention also proposes a process for preparing a panoramic sunroof dimming film to eliminate cabin reflections, comprising the following steps: S1. Preparation of epoxy-segregated modified AR antireflective film: A roll-to-roll double-layer coating process is adopted, in which a low refractive index layer and a high refractive index layer containing segregating agent are coated sequentially. After gradient drying and UV curing, epoxy functional groups are oriented and enriched on the bonding surface to obtain modified AR antireflective film, which is then rolled up for use. S2. Preparation of modified PET substrate: The PET substrate is subjected to single-sided shielding plasma treatment on both sides in steps to complete the amino grafting modification on the AR side, the hydroxyl modification on the electrode side and the anchoring of triethoxysilyl-terminated polythiophene oligomers, and the release film is applied on both sides and then rolled up for later use. S3. Preparation of PEDOT:PSS conductive electrode and physical entanglement interface: After coating the electrode side of the modified PET substrate with triethoxysilyl-terminated polythiophene oligomer, PEDOT:PSS conductive liquid is coated and a molecular entanglement interface is formed during the gradient drying process. S4. Adhesive-free lamination: The bonding surface of the modified AR film is aligned with the AR side of the modified PET substrate, and the interface covalent bonding is completed by hot roller bonding and constant temperature curing to obtain an integrated substrate. S5. Preparation of outer composite substrate: The PEDOT:PSS transparent conductive electrode layer is combined with the outer substrate protective layer to obtain the outer composite substrate. S6. Preparation of PDLC dimming functional layer: PDLC mixture is coated on the electrode side of modified PET substrate, and after being laminated with the outer composite substrate, it is cured by UV curing and cut to obtain the finished panoramic sunroof dimming film.
[0020] Preferably, in step S1, a roll-to-roll double-layer gravure coating machine is used for coating, and the coating speed is 2.5 to 3.5 m / min; The drying process uses a 5-section gradient drying tunnel with temperatures of 50℃, 70℃, 80℃, 70℃, and 50℃ respectively. UV curing is performed using a high-pressure mercury lamp, with a curing energy of 300–400 mJ / cm². 2 ; The amount of epoxy segregating agent added is 2% to 3% of the solid content of the high refractive index layer resin.
[0021] Preferably, in step S2, the power of the atmospheric pressure oxygen plasma treatment is 2.5 to 3.5 kW, the working gas is an argon-oxygen mixture with a volume ratio of 9:1, and the treatment speed is 2.5 to 3.5 m / min. The AR side amino grafting adopts a single-sided dip-coating process. The dip-coating solution is a 2wt% γ-aminopropyltriethoxysilane ethanol aqueous solution. After dip-coating, it is dried with hot air at 70-90℃ for 2 minutes. The electrode side of the modified PET substrate is coated with triethoxysilyl-terminated polythiophene oligomer by single-sided gravure printing. The primer is an ethanol solution of 0.5 wt% triethoxysilyl-terminated polythiophene oligomer. After coating, the substrate is dried with hot air at 90-110°C for 3 minutes to complete the anchoring.
[0022] Preferably, in step S3, the PEDOT:PSS conductive liquid is coated using a slot extrusion coating process with a coating speed of 1.5 to 2.5 m / min; the drying process uses a three-stage gradient drying tunnel with temperatures of 60°C for 2 min, 90°C for 2 min, and 110°C for 3 min. The PEDOT:PSS conductive liquid contains 4-5 wt% dimethyl sulfoxide as a conductivity enhancer.
[0023] Preferably, in step S4, an optical-grade hot roller laminator is used for lamination, and the lamination environment is a Class 100 cleanroom with a temperature of 23±2℃ and a relative humidity of ≤40%. The hot roller bonding temperature is 70-80℃, the bonding pressure is 0.3-0.4MPa, and the bonding speed is 1.2-1.8m / min. After bonding, the mixture is cured in a constant temperature environment of 75-85℃ for 20-28 hours to achieve complete covalent bonding at the interface.
[0024] Compared with the prior art, the beneficial effects of the present invention are: 1. The optical root cause of cockpit reflections lies in the macroscopic interface with abrupt refractive index changes within the laminated structure. Existing technology uses OCA optical adhesive to bond the AR film to the PET substrate, inevitably introducing two additional refractive index abrupt interfaces: AR film / adhesive layer and adhesive layer / PET substrate. Even with a very small refractive index difference between the adhesive layer and PET, according to Fresnel's equations, perceptible residual reflections will still occur under oblique incidence or broad spectral conditions, superimposing to form reflections of people or objects within the cockpit. This invention, however, uses an epoxy ring-opening reaction to directly covalently bond the AR film and PET substrate, eliminating the intermediate macroscopic adhesive layer interface. At this point, although the refractive index differs between the high-refractive-index layer of the AR film and the modified PET, the chemical bonding eliminates discrete physical interfaces, suppressing light reflection in the transition region and forming a sub-optical wavelength refractive index gradient layer. The bonding surface achieves a high-density epoxy functional group localized reaction with the segregating agent, resulting in a dense and uniform transition zone. There is no scattering caused by uneven adhesive layer thickness or microbubbles, thus eliminating the interface reflection channel caused by reflection from a mechanistic perspective.
[0025] 2. Existing technologies rely on organic acrylate pressure-sensitive adhesives for interlayer bonding. However, the bottleneck in durability lies in the sensitivity of ester groups to humid and hot environments. Under high temperature and humidity cycling conditions in vehicles, ester groups hydrolyze to generate carboxylic acids, which in turn catalyze polymer chain breakage and produce chromophores, leading to yellowing of the adhesive layer and increased haze. Simultaneously, as a viscoelastic material, the adhesive layer is prone to molecular chain slippage under long-term creep and thermal stress, resulting in decreased peel strength and edge bubbles. The adhesive-free covalent bonding layer between the AR film and PET in this invention is formed by β-hydroxy ether bonds and amine bonds through ring-opening of epoxy and amino groups. Its covalent bond energy exceeds 300 kJ / mol, exhibiting thermodynamic stability far superior to van der Waals forces and hydrogen bonds. Furthermore, it eliminates the need for small molecule plasticizers or initiators, thus avoiding interfacial hydrolysis and thermal degradation. Secondly, the substrate electrode bonding layer on the electrode side utilizes the π-π stacking and multiple physical entanglements between the anchored thiophene long chains and the PEDOT:PSS conjugated main chain to dissipate stress during thermal shock through the coordinated movement of chain segments, unlike the adhesive layer which forms stress concentration points at the interface leading to damage. Therefore, the entire film can still maintain its initial peel strength, high light transmittance, and low haze after severe aging.
[0026] 3. Existing methods for enhancing the bonding between PET and PEDOT:PSS typically require coating with a silicone primer or using an insulating adhesive resin. This inserts a low-dielectric-constant, high-barrier insulating layer between the PET and the electrode. This insulating layer not only blocks the longitudinal pathway of charge carrier transport from the electrode to the current collector but also increases the contact resistance due to the interfacial capacitance effect, leading to a significant increase in electrode sheet resistance and driving voltage. This invention addresses this by covalently anchoring one end of a triethoxysilyl-terminated polythiophene oligomer to the PET surface, while the other end undergoes π-π conjugation with the thiophene rings on the PEDOT:PSS backbone. This physically entangled interface provides a continuous delocalized electron transport channel, rather than an electrical discontinuity, allowing holes to be efficiently injected from the PEDOT-rich phase into the conductive network of the PET surface via the thiophene chain. This enables the electrode to achieve high conductivity retention and stably maintain a low sheet resistance without additional sintering after composite bonding.
[0027] In summary, this invention achieves the elimination of macroscopic adhesive layer interfaces through chemical bonding and the elimination of cabin reflections by using a completely adhesive-free interface design; it replaces pressure-sensitive adhesives that are prone to hydrolysis and aging with covalent bonds and molecular entanglement, thus eliminating the risk of yellowing and peeling failure; and it replaces the insulating primer with a conductive entanglement layer, thereby maintaining high interface adhesion and high conductivity. Attached Figure Description
[0028] Figure 1 This is a schematic diagram of the layered structure of the panoramic sunroof dimming film for eliminating cabin reflections as described in this invention; Figure 2 This is a production process flow diagram of the modified AR antireflective film for the panoramic sunroof dimming film described in this invention. Figure 3 This is a production process flow diagram of the integrated substrate of the panoramic sunroof dimming film described in this invention; Figure 4 This is a flowchart illustrating the manufacturing process of the outer composite substrate of the panoramic sunroof dimming film described in this invention. In the figure: 1 is the modified AR antireflective film layer, 2 is the modified PET substrate layer, 3 is the PEDOT:PSS transparent conductive electrode layer, 4 is the PDLC dimming functional layer, 5 is the PEDOT:PSS transparent conductive electrode layer, and 6 is the outer substrate protective layer. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0030] Example 1: Modified AR antireflective film: low-refractive-index fluorinated acrylate layer n=1.37, dry film thickness 85nm; high-refractive-index silicone acrylate layer n=1.63, dry film thickness 105nm; epoxy segregating agent added at 2% of the resin solid content of the high-refractive-index layer, epoxy functional group density on the bonding surface 2.5nm / cm³ 2 .
[0031] Modified PET substrate: 180μm optical PET; γ-aminopropyltriethoxysilane grafted onto the AR side after plasma etching, with an amino density of 2.6 nmol / cm³. 2 ; 0.5wt% triethoxysilyl-terminated polythiophene oligomer (Mn=1500) is anchored on the electrode side.
[0032] PEDOT Electrode and Interface: The electrode dry film thickness is 90nm, the PEDOT coating solution is enriched with 4wt% DMSO, and the sheet resistance of the finished product is 170Ω / sq; a thiophene segment physical entanglement interface is formed between the electrode and the substrate.
[0033] Adhesive-free lamination process: hot roller bonding temperature 70℃, bonding pressure 0.3MPa, machine speed 1.8m / min; covalent bonding is completed by constant temperature curing at 75℃ for 20h.
[0034] Functional layer and outer substrate: PDLC dimming layer with a thickness of 12μm and nematic liquid crystal accounting for 65wt%; the outer side is a 120μm optical PET substrate, matched with PEDOT:PSS transparent electrode.
[0035] Example 2: Modified AR antireflective film: Low-refractive-index fluorinated acrylate layer n=1.38, dry film thickness 90nm; High-refractive-index silicone acrylate layer n=1.65, dry film thickness 110nm; Epoxy segregating agent added at 2.5% of the resin solid content of the high-refractive-index layer, epoxy functional group density on the bonding surface 3.0 nmol / cm³ 2 .
[0036] Modified PET substrate: 188μm optical PET; γ-aminopropyltriethoxysilane grafted onto the AR side after plasma etching, with an amino density of 3.1 nmol / cm³. 2 ; 0.5wt% triethoxysilyl-terminated polythiophene oligomer (Mn=2000) is anchored on the electrode side.
[0037] PEDOT Electrode and Interface: The electrode dry film thickness is 100nm, the PEDOT coating solution contains 4.5wt% DMSO, and the sheet resistance of the finished product is 150Ω / sq; a thiophene segment physical entanglement interface is formed between the electrode and the substrate.
[0038] Adhesive-free lamination process: hot roller bonding temperature 75℃, bonding pressure 0.35MPa, machine speed 1.5m / min; covalent bonding is completed by constant temperature curing at 80℃ for 24h.
[0039] Functional layer and outer substrate: PDLC dimming layer with a thickness of 15μm and nematic liquid crystal accounting for 70wt%; the outer side is a 125μm optical PET substrate, matched with PEDOT:PSS transparent electrode.
[0040] Example 3: Modified AR antireflective film: Low-refractive-index fluorinated acrylate layer n=1.39, dry film thickness 95nm; High-refractive-index silicone acrylate layer n=1.67, dry film thickness 115nm; Epoxy segregating agent added at 3% of the resin solid content of the high-refractive-index layer, epoxy functional group density on the bonding surface 3.5nm / cm³ 2 .
[0041] Modified PET substrate: 200μm optical PET; γ-aminopropyltriethoxysilane grafted onto the AR side after plasma etching, with an amino density of 3.4 nmol / cm³. 2 ; 0.5wt% triethoxysilyl-terminated polythiophene oligomer (Mn=2500) is anchored on the electrode side.
[0042] PEDOT Electrode and Interface: The electrode dry film thickness is 110nm, the PEDOT coating solution contains 5wt% DMSO, and the sheet resistance of the finished product is 130Ω / sq; a thiophene segment physical entanglement interface is formed between the electrode and the substrate.
[0043] Adhesive-free lamination process: hot roller bonding temperature 80℃, bonding pressure 0.4MPa, machine speed 1.2m / min; covalent bonding is completed by constant temperature curing at 85℃ for 28h.
[0044] Functional layer and outer substrate: PDLC dimming layer with a thickness of 18μm and nematic liquid crystal accounting for 75wt%; the outer side is a 130μm optical PET substrate, matched with PEDOT:PSS transparent electrode.
[0045] The following comparison model was also set: Comparative Example 1: The current mainstream production solution for automotive PDLC dimming film is adopted: ordinary double-layer AR film, 50μm OCA optical adhesive bonded to ordinary PET substrate, PEDOT:PSS electrode directly coated, no covalent bonding, no physical entanglement of triethoxysilyl-terminated polythiophene oligomers, and the parameters of PDLC functional layer and outer substrate are completely consistent with those of Example 2.
[0046] Comparative Example 2: The modified AR antireflective film, modified PET substrate, and triethoxysilyl-terminated polythiophene oligomer entangled electrode of the present invention are used. The only difference is that the adhesive-free covalent bonding is replaced with 50μm OCA optical adhesive bonding. The other raw materials and process parameters are completely consistent with those of Example 2.
[0047] Comparative Example 3: Using the modified AR film, adhesive-free covalent bonding, and modified PET substrate of the present invention, only the triethoxysilyl-terminated polythiophene oligomer primer is removed on the electrode side, and the PEDOT:PSS electrode is directly coated on the hydroxyl-modified PET surface, with no physical entanglement interface. The other parameters are completely consistent with those of Example 2.
[0048] Comparative Example 4: The present invention employs adhesive-free covalent bonding, modified PET substrate, and long-chain entangled electrodes. Only the AR film does not contain epoxy segregating agent. It uses a common high-refractive-index organosilicon layer and is directly pressed after plasma activation before bonding. The remaining parameters are completely consistent with those of Example 2.
[0049] Performance testing: Table 1. Summary of data for each experimental group Data Analysis: Compared with existing mainstream mass-produced dimming film solutions, the complete technical solution of this invention has achieved significant improvements in core anti-aliasing performance, interface reliability, and long-term electrode stability. The core dimming performance is on par with existing technologies, while the impact resistance mechanical properties are slightly reduced, which meets the design expectations.
[0050] By comparing Example 2 with Comparative Example 1, we can see that: Comparative Example 1 is the current mainstream mass production solution for automotive panoramic sunroof dimming film. The core difference between it and Example 2 is that it uses a common double-layer AR film, OCA optical adhesive bonding, direct coating of PEDOT electrodes, epoxy-free segregated AR structure, adhesive-free covalent bonding layer, and a design of triethoxysilyl-terminated polythiophene oligomer physical entanglement interface.
[0051] In terms of optical performance, the average visible light reflectance of the cockpit side in Example 2 is only 0.85%, which is much lower than 2.13% in Comparative Example 1, a reduction of 60.1%. This achieves the design goal of a total interface reflectance of less than 1%, which can significantly reduce the mirror reflection of the instrument panel and central control screen in the cockpit on the sunroof. At the same time, the visible light transmittance is increased by 2.3 percentage points, and the transparent haze is reduced by 0.23 percentage points, resulting in a better optical appearance.
[0052] Regarding interface reliability, the 180° peel strength of the AR layer-substrate in Example 2 reached 14.7 N / 25 mm, which is 72.9% higher than that of Comparative Example 1. After 1000 hours of humid heat aging at 85°C / 85%RH, the reflectivity change rate was only 3.1%, which is much lower than the 12.6% of Comparative Example 1. The electrode adhesion remained at level 0, with no risk of delamination or detachment.
[0053] Meanwhile, the PDLC dimming response time and contrast of Example 2 are basically the same as those of Comparative Example 1, and the electrode conductivity retention rate reaches 97.1%, without negatively affecting the core dimming function; due to the removal of the elastic OCA buffer layer, microcracks appeared on the film surface during the drop ball impact test, and the impact resistance mechanical properties are slightly reduced compared with the prior art.
[0054] Overall, the complete solution of this invention can significantly improve the cabin anti-shadow effect and long-term interface reliability while maintaining the same core dimming performance as existing technologies, thus meeting the needs of vehicle use.
[0055] By comparing Example 2 with Comparative Example 2, we can see that: Both groups used the same raw materials and process parameters. The variable was that Comparative Example 2 retained a 50μm OCA optical adhesive to achieve bonding between the AR film and the substrate, and did not use an adhesive-free covalent bonding structure. In terms of optical performance, the average visible light reflectance of the cockpit side of Comparative Example 2 was 1.42%, which was lower than the traditional solution, but still significantly higher than the 0.85% of Example 2. Example 2 reduced the reflectance by 40.1% by eliminating the OCA adhesive layer, thus reducing the two additional optical reflection interfaces of AR film-OCA and OCA-substrate. This is the core technical means to achieve a reflectance breakthrough of 1%. At the same time, Example 2 increased the visible light transmittance by 1.5 percentage points and reduced the haze by 0.14 percentage points, eliminating the optical loss caused by the OCA adhesive layer.
[0056] In terms of bonding reliability, the interface stability of covalent bonding is far superior to that of OCA physical bonding, which can effectively alleviate the problems of interface debonding and increased reflectivity under long-term humid and hot conditions. Therefore, the interlayer peel strength of Example 2 reached 14.7 N / 25 mm, which is 59.8% higher than that of Comparative Example 2 (9.2 N / 25 mm). After 1000 hours of humid and hot aging, the reflectivity change rate of Comparative Example 2 was 7.8%, which is 2.5 times that of Example 2.
[0057] By comparing Example 2 and Comparative Example 3, we can see that: The AR film structure, glue-free bonding process, and substrate modification scheme of the two groups are the same. The variable is that the triethoxysilyl-terminated polythiophene oligomer on the electrode side of Comparative Example 3 is removed, and the PEDOT:PSS electrode is directly coated on the surface of the modified substrate, without the physical entanglement interface of thiophene segments.
[0058] Regarding electrode adhesion, the physical entanglement structure of the triethoxysilyl-terminated polythiophene oligomer can significantly improve the interfacial bonding force between the substrate and the electrode. The PEDOT electrode in Example 2 initially had a cross-cut adhesion of grade 0, and it maintained grade 0 after 1000 hours of humid heat aging at 85°C / 85%RH. In contrast, the initial adhesion of Comparative Example 3 was only grade 2, and it further decreased to grade 3 after aging, indicating a significant risk of electrode delamination.
[0059] In terms of conductivity and dimming performance, the physical entanglement scheme does not destroy the conjugated backbone and doped state of PEDOT:PSS. It achieves improved adhesion with almost no loss of conductivity and avoids the problem of significant attenuation of electrode conductivity caused by traditional chemical bonding. The electrode conductivity retention rate of Example 2 is 97.1%, which is only slightly different from the 100% of Comparative Example 3. The dimming response time and contrast of PDLC are basically the same as those of Comparative Example 3.
[0060] Furthermore, there were no significant differences in optical reflectivity and haze parameters between the two groups, proving that the modification of the electrode interface does not interfere with the anti-reflection and anti-shadow effect of the AR film.
[0061] In summary, the physical entanglement interface of triethoxysilyl-terminated polythiophene oligomers can significantly improve the long-term reliability of the electrode interface while maintaining anti-reflective optical performance, electrode conductivity, and dimming function, thus solving the industry pain point of insufficient adhesion of PEDOT electrodes.
[0062] By comparing Example 2 with Comparative Example 4, we can see that: The two groups had the same glue-free bonding process, substrate modification, and electrode entanglement scheme. The variable was that the AR film of Comparative Example 4 did not have epoxy segregating agent added, and the bonding surface had no directional enriched epoxy functional groups. It was only activated by plasma and then pressed with the amino-modified substrate.
[0063] In terms of optical performance, the average visible light reflectance of Comparative Example 4 on the cockpit side was 1.21%, which was higher than 0.85% of Example 2. It did not reach the design target of reflectance of less than 1%. Without epoxy functional group segregation, the AR film and the substrate could not form a uniform and dense covalent bond interface. There were gaps and air layers at the interface on the micro-nano scale, which increased interface reflection and weakened the anti-reflection and anti-shadow effect of the AR film.
[0064] Regarding interface reliability, the peel strength of the AR layer-substrate of Comparative Example 4 was only 6.8 N / 25 mm, which was much lower than the 14.7 N / 25 mm of Example 2. After 1000 hours of damp heat aging, the reflectivity change rate of Comparative Example 4 reached 8.9%, which was 2.9 times that of Example 2. After long-term use, it is easy to have problems such as local delamination of the interface and attenuation of the anti-reflection effect.
[0065] In summary, the epoxy-directed segregation of modified AR films is a prerequisite for achieving uniform glue-free covalent bonding and a core foundation for ensuring the achievement of anti-reflection optical effects and long-term interface stability.
[0066] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A panoramic sunroof dimming film for eliminating cabin reflections, characterized in that, The following layers are stacked sequentially from the inside of the cabin to the outside of the vehicle: modified AR anti-reflective film layer, modified PET substrate layer, PEDOT:PSS transparent conductive electrode layer, PDLC dimming function layer, PEDOT:PSS transparent conductive electrode layer, and outer substrate protective layer. The bonding surface of the modified AR antireflective film is enriched with epoxy functional groups by an epoxy segregating agent. The modified PET substrate has amino functional groups grafted onto the side facing the AR film, and the side facing the electrode is anchored with a long chain structure containing thiophene segments by a triethoxysilyl-terminated polythiophene oligomer. The modified AR antireflective film layer and the modified PET substrate layer are bonded together by a covalent bond structure formed by the ring-opening reaction of epoxy groups and amino groups without glue. The modified PET substrate is bonded to the interface formed by the thiophene segments and the PEDOT:PSS conjugated main chain; The outer substrate protective layer is a PET substrate modified with triethoxysilyl-terminated polythiophene oligomer only on the side facing the electrode.
2. The panoramic sunroof dimming film for eliminating cabin reflections according to claim 1, characterized in that, The modified AR antireflective film has a double-layer interference structure, consisting of a low-refractive-index fluorinated acrylate layer on the air side, a high-refractive-index silicone acrylate layer on the bonding side, and an epoxy segregating agent added to the silicone acrylate layer. Epoxy functional groups are enriched on the bonding surface of the high-refractive-index layer through surface segregation, with an epoxy functional group density of 2.5–3.5 nmol / cm³. 2 ; The refractive index of the fluorinated acrylate layer is 1.37–1.39, and the dry film thickness is 85–95 nm; the refractive index of the organosilicon acrylate layer is 1.63–1.67, and the dry film thickness is 105–115 nm.
3. The panoramic sunroof dimming film for eliminating cabin reflections according to claim 1, characterized in that, The modification process of the modified PET substrate includes: The side facing the AR film is frequently etched with oxygen plasma and then grafted with γ-aminopropyltriethoxysilane. After the side facing the electrode is frequently etched with oxygen plasma to introduce hydroxyl groups, a triethoxysilane-terminated polythiophene oligomer is anchored, and its thiophene segments extend outward.
4. The panoramic sunroof dimming film for eliminating cabin reflections according to claim 1, characterized in that, The epoxy segregating agent is an epoxy-terminated fluorocarbon acrylate oligomer, and its preparation steps are as follows: Fluorinated acrylate monomers, epoxy acrylate monomers, and azobisisobutyronitrile initiator were weighed according to a mass ratio of 72-78:18-22:3-6, mixed, and then anhydrous ethanol was added to prepare a reaction system with a solid content of 20%. Free radical polymerization was carried out at a constant temperature of 78-82℃ for 7-9 hours under nitrogen protection. After precipitation with n-hexane and vacuum drying, epoxy segregating agent was obtained. The fluorinated acrylate monomer is hexafluorobutyl methacrylate or hexafluorobutyl acrylate; the epoxy acrylate monomer is glycidyl methacrylate. The number-average molecular weight of the epoxy segregating agent is 1500-2500, the epoxy equivalent is 700-900, the fluorine content is 15-20wt%, and the surface energy is ≤22mN / m. The preparation method of the triethoxysilyl-terminated polythiophene oligomer specifically includes the following steps: Under anhydrous and oxygen-free conditions, 2,5-dibromo-3-hexylthiophene was dissolved in dry tetrahydrofuran, and isopropyl magnesium chloride was added dropwise at low temperature to carry out Grignard exchange. The mixture was stirred at room temperature for 1 to 2 hours. Ni(dppp)Cl2 catalyst was added, and the temperature was raised to reflux to carry out Kumada cross-coupling polymerization. The degree of polymerization was controlled at 3 to 6 thiophene rings by controlling the molar ratio of 2,5-dibromo-3-hexylthiophene to isopropyl magnesium chloride at 30 to 50:
1. After polymerization, the reaction was terminated by end capping with vinyl magnesium bromide, precipitated in methanol, purified and dried to obtain a polythiophene oligomer with vinyl at one end and hydrogen or bromine at the other end. Polythiophene oligomers are obtained by converting vinyl groups to hydroxyl groups through a hydroboration-oxidation reaction; Hydroxyl-terminated polythiophene oligomers were dissolved in an anhydrous solvent. 3-isocyanate-propyltriethoxysilane and 2%–4% (by mass) of dibutyltin dilaurate (based on the total mass of 3-isocyanate-propyltriethoxysilane and the hydroxyl-terminated polythiophene oligomers) were added at a molar ratio of hydroxyl to isocyanate group = 1:1.1–1.
3. The mixture was reacted at 60–70 °C for 4–6 hours, followed by vacuum distillation, purification, and drying to obtain triethoxysilyl-terminated polythiophene oligomers.
5. The panoramic sunroof dimming film for eliminating cabin reflections according to claim 1, characterized in that, The material specifications for each functional layer meet the following requirements: The dry film thickness of the PEDOT:PSS transparent conductive electrode is 90-110 nm, and the sheet resistance is 130-170 Ω / sq. The thickness of the PDLC dimming functional layer is 12-18 μm, wherein the mass ratio of nematic liquid crystal is 65%-75%, and the prepolymer is aliphatic polyurethane acrylate. The modified PET substrate layer has an optical-grade PET substrate with a thickness of 180–200 μm. The outer substrate protective layer is made of 120-130 μm thick optical-grade PET substrate.
6. A manufacturing process for a panoramic sunroof dimming film for eliminating cabin reflections as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Preparation of epoxy-segregated modified AR antireflective film: A roll-to-roll double-layer coating process is adopted, in which a low refractive index layer and a high refractive index layer containing segregating agent are coated sequentially. After gradient drying and UV curing, epoxy functional groups are oriented and enriched on the bonding surface to obtain modified AR antireflective film, which is then rolled up for use. S2. Preparation of modified PET substrate: The PET substrate is subjected to single-sided shielding plasma treatment on both sides in steps to complete the amino grafting modification on the AR side, the hydroxyl modification on the electrode side and the anchoring of triethoxysilyl-terminated polythiophene oligomers, and the release film is applied on both sides and then rolled up for later use. S3. Preparation of PEDOT:PSS conductive electrode and physical entanglement interface: After coating the electrode side of the modified PET substrate with triethoxysilyl-terminated polythiophene oligomer, PEDOT:PSS conductive liquid is coated and a molecular entanglement interface is formed during the gradient drying process. S4. Adhesive-free lamination: The bonding surface of the modified AR film is aligned with the AR side of the modified PET substrate, and the interface covalent bonding is completed by hot roller bonding and constant temperature curing to obtain an integrated substrate. S5. Preparation of outer composite substrate: The PEDOT:PSS transparent conductive electrode layer is combined with the outer substrate protective layer to obtain the outer composite substrate. S6. Preparation of PDLC dimming functional layer: PDLC mixture is coated on the electrode side of modified PET substrate, and after being laminated with the outer composite substrate, it is cured by UV curing and cut to obtain the finished panoramic sunroof dimming film.
7. The preparation process according to claim 6, characterized in that, In step S1, a roll-to-roll double-layer gravure coating machine is used for coating, and the coating speed is 2.5 to 3.5 m / min. The drying process uses a 5-section gradient drying tunnel with temperatures of 50℃, 70℃, 80℃, 70℃, and 50℃ respectively. UV curing is performed using a high-pressure mercury lamp, with a curing energy of 300–400 mJ / cm². 2 ; The amount of epoxy segregating agent added is 2% to 3% of the solid content of the high refractive index layer resin.
8. The preparation process according to claim 6, characterized in that, In step S2, the power of the atmospheric pressure oxygen plasma treatment is 2.5 to 3.5 kW, the working gas is an argon-oxygen mixture with a volume ratio of 9:1, and the treatment speed is 2.5 to 3.5 m / min. The AR side amino grafting adopts a single-sided dip-coating process. The dip-coating solution is a 2wt% γ-aminopropyltriethoxysilane ethanol aqueous solution. After dip-coating, it is dried with hot air at 70-90℃ for 2 minutes. The electrode side of the modified PET substrate is coated with a single-sided gravure coating. The primer is an ethanol solution of 0.5 wt% triethoxysilyl-terminated polythiophene oligomer. After coating, the substrate is dried with hot air at 90-110°C for 3 minutes to complete the anchoring.
9. The preparation process according to claim 6, characterized in that, In step S3, the PEDOT:PSS conductive liquid is coated using a slot extrusion coating process with a coating speed of 1.5–2.5 m / min; the drying process uses a three-stage gradient drying tunnel with temperatures of 60℃ for 2 min, 90℃ for 2 min, and 110℃ for 3 min. The PEDOT:PSS conductive liquid contains 4-5 wt% dimethyl sulfoxide as a conductivity enhancer.
10. The preparation process according to claim 6, characterized in that, In step S4, an optical-grade hot roller laminator is used for lamination in a Class 100 cleanroom with a temperature of 23±2℃ and a relative humidity of ≤40%. The hot roller bonding temperature is 70-80℃, the bonding pressure is 0.3-0.4MPa, and the bonding speed is 1.2-1.8m / min. After bonding, the mixture is cured in a constant temperature environment of 75-85℃ for 20-28 hours to achieve complete covalent bonding at the interface.
Citation Information
Patent Citations
PET (Polyethylene Terephthalate) for electrochromic dimming film and preparation method of PET
CN121578562A
Anti-dazzle scratch-resistant optical conductive composite film and preparation method thereof
CN122050924A